Evaluation of ultrasound by direct contact on convective drying of banana (Musa paradisiaca) slices using Principal Component Analysis and Response Surface Methodology (2019)
Conventional convective drying is one of the latest techniques used to reduce the amount of water in foods, however, due to the long times of exposure to high temperatures, these techniques can reduce the sensory quality, in addition to generating high costs associated with consumption of energy. An alternative to improve efficiency in these processes is to use innovative tools such ultrasound (US) application by using direct contact during drying to improve quality and keep nutritional content of the product with reduction in time, cost and temperatures of operation.